Improvement of Arterial Wall Lesions in Parallel with Decrease of Plasma Pentraxin-3 Levels in a Patient with Refractory Takayasu Arteritis after Treatment with Tocilizumab - Shiho Iwagaitsu; Taio Naniwa (Case Reports in Rheumatology)
A 19-year-old Japanese woman with active Takayasu arteritis despite multiple conventional immunosuppressive therapies with glucocorticoids in combination with intravenous cyclophosphamide, azathioprine, or infliximab with methotrexate and tacrolimus was successfully treated by switching from infliximab to intravenous tocilizumab. Worsening of claudication of the legs and elevated acute phase reactants, including plasma pentraxin-3 levels, were observed during combination therapy with infliximab. Computed tomography demonstrated increased wall thickening with contrast enhancement in the preexisting lesion of the descending aorta and the femoral arteries. After switching from infliximab to tocilizumab, plasma pentraxin-3 levels gradually decreased to the normal range in parallel with the improvement of claudication. Follow-up computed tomographic scans confirmed the marked improvement of these arterial lesions. Moreover, plasma pentraxin-3 level was increased in response to the worsening of claudication that occurred just after switching to a subcutaneous tocilizumab injection. Measurements of plasma pentraxin-3 might be useful for evaluation of the vascular wall inflammation and therapeutic efficacy even during biologic therapy targeting tumor necrosis factor α and interleukin-6.